Faktor-Faktor Yang Berhubungan Dengan Kejadian Asfiksia Di RS PKU Muhammadiyah Karanganyar Tahun 2023 - Siti Mulyani; Suyani (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Indonesia recorded cases of infant mortality (IMR) which most of the deaths occurred during the neonatal period (0-28 days) was 18,281 deaths. Infant mortality aged 0-7 days was 75.5%. The most common cause of neonatal death in 2022 was asphyxia (25.3%). Asphyxia occurs due to lack of blood flow or oxygen exchange to or from the fetus in newborn babies, resulting in hypoxia of the baby in the womb. The aim of this research is to determine the factors associated with the incidence of asphyxia at PKU Muhammadiyah Hospital. The research method was quantitative with a case control design. Samples or respondents were taken using the purposive sampling method, namely a sample determination technique with certain considerations as the sample number was 138 respondents. The research instrument employed by using a master data table sheet via medical records. Data were analyzed from a sample of 69 cases and 69 controls by having univariate and bivariate analysis techniques using the chi- square odd ratio test. The results of statistical tests showed that there were several variables that had a p value of 0.000, which means <0.05, including: Mother's age, Gestational age, Type of delivery, PROM, LBW and parity variables had a p value of 0.001. The conclusion is that there is a relationship between the factors that cause asphyxia at PKU Muhammadiyah Karanganayar Hospital, including parity, gestational age, maternal age, type of delivery, LBW, and PROM.